Automated Weed Detection for Sustainable Agriculture Using CNN and Image Processing - K. Uthra Devi (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Farming serves as the primary source of income for more than half of the Indian population. One of the major challenges in agriculture is the effective control of weeds in plantation crops. Currently, weeds are managed through manual labour or by applying herbicides across the entire field. This method is inefficient, as it leads to environmental pollution and poses health risks to humans. To mitigate these issues, a smart weed control system using Convolutional Neural Networks (CNN), image processing, and IoT is proposed. The CNN model is trained using a large dataset of weed and crop images. This trained model is deployed on a Raspberry Pi for real-time weed detection. The captured images are segmented using the Watershed Segmentation Algorithm, and each segment is classified as weed or crop using the CNN model. The detected weed regions are highlighted and sent to farmers via email for further action. The system was evaluated using 250 images and achieved an average accuracy of 85%, a false ratio of 7%, and a false acceptance ratio of 2.6%.